Analysis of Education and Economic Development: Mapping Research on The Scopus Database in Indonesia - Putra Cahyono, Jordan (Journal of Economics Development Issues, 2024)
Indonesia has made notable advancements in the development of its educational infrastructure. However, persistent challenges pertaining to educational equity and quality continue to impede economic progress. The objective of this study is to map the research on the relationship between education and economic development in Indonesia using the Scopus database from 1965 to 2024. The study employs bibliometric analysis to examine trends, themes, and research gaps across 920 articles. The findings indicate a notable surge in research activity following 2015, with pivotal themes encompassing educational inequality and regional disparities. These implications highlight the necessity for targeted policy interventions and future research that employs a longitudinal and interdisciplinary approach in order to support informed policymaking and strategic planning for Indonesia's educational and economic development.